Ultrafast and Ultrasensitive Simultaneous Molecular Recognition and Quantification of CA12-5, CA72-4, HER1, and AFP in Biological Samples - Ruxandra-Maria Ilie-Mihai; Raluca-Ioana Stefan-van Staden; Bianca-Maria Tuchiu-Stanca (Chemosensors)
Simultaneous molecular recognition and quantification of at least four biomarkers in biological samples may contribute to early and fast diagnosis of illnesses such as cancer. The electrodes able to reliably perform on-site these tests are the stochastic sensors. Therefore, three novel 3D stochastic sensors employing carbon-based powders (graphite, graphene, nanographene) treated with N-(2-mercapto-1H-benzo[d]imidazole-5-yl) oleamide solution were used for screening tests of whole blood, gastric tumoral tissue, urine, and saliva for molecular recognition and quantification of CA12-5, CA72-4, HER1, and AFP. The best performance was achieved for the sensor based on graphene, when the highest sensitivities were recorded, on wide working concentration ranges of: 8.37 × 10−14–8.37 U mL−1 for CA12-5, 4.00 × 10−11–4.00 × 10−3 U mL−1 for CA72-4, 3.90 × 10−16–3.90 × 10−6 g mL−1 for HER1, and 3.00 × 10−20–3.00 × 10−6 g mL−1 for AFP. The wide linear concentration ranges cover levels of biomarkers found in gastric cancer patients from early to late stages. The recovery values were higher than 98.00 with %, RSD lower than 1.00%.